ANALYSIS OF CONSUMER PERCEPTION AND CONSUMER INTEREST TOWARD PURCHASE DECISION AT SWALAYAN 88 MEDAN - Erina Alimin; Eddy, Eddy; Sri Aprianti Tarigan; Susanto, Susanto; Bestadrian Prawiro Theng (Media Bina Ilmiah, 2024)
The purpose of this study was to determine the effect of consumer perceptions and consumer interest on purchasing decisions at Brastagi Supermarket Manhattan Times Square Medan. This research is a type of quantitative research. The population in this study are all consumers who make purchases at the Swalayan 88 Medan, the number of which is unknown. The sampling technique using the Lemeshow sampling technique obtained as many as 96 research samples. The method of collecting data in this research is literature study and questionnaires. Methods of data analysis using descriptive analysis and simple linear regression analysis. The results showed that the value of tcount (7.483) > ttable (1.985) with a significance of 0.000 ttable (1.985) with a significance of 0.042 Ftable (3.07) with a significant level of 0.00 < 0.05 so that it can be interpreted that H3 is accepted with the understanding that there is an influence between Consumer Perceptions and Consumer Interests on Purchase Decisions